Nasr Hamid Abu Zayd's Hermeneutics - Azhar, Azhar; Zulkarnaen (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Nasr Hamid Abu Zaid is one of the most influencial figure of hermeneutics in the muslim world. Among his thoughts there are several pros and cons among muslims. What is quite well known is that Alquran is a muntaj saqafi (cultural product) and a muntij saqafi (cultural producer). He also interpreted the concept of jinn with a new understanding from what society had previously believed (demitology). This paper aims to reveal the concept of hermeneutics offered by Nasr. The method used in this journal is qualitative descriptive analysis, through literature studies of documents and previous research texts. The primary data source is Nasr’s works and secondary data obtained from commentaries and several journals on Nasr's thought. This journal also tries to explain Nasr's main thoughts by first knowing the educational background surrounding it. So, the product of his thinking cannot be separated from his background, namely Arabic language and literature, which causes him to continue trying to explore the contents of Alquran by studying in detail aspects of its language.